The great stink : how Joseph Bazalgette solved London's poop pollution problem - Paeff, Colleen (Margaret K. McElderry Books, 2021)
Presents a nonfiction picture book illustrating how in 1858, an engineer named Joseph Bazalgette had an idea for fixing the sewage system in the city of London and cleaning up the smelly River Thames. He also aimed to reduce cholera outbreaks that were continually affecting the city. Recounts how he brought his ideas to fruition, and offers a timeline, further reading, and tips for readers on how to prevent pollution in their communities today.